2011
DOI: 10.1093/humrep/der256
|View full text |Cite
|
Sign up to set email alerts
|

The use of morphokinetics as a predictor of embryo implantation

Abstract: The image acquisition and time-lapse analysis system makes it possible to determine exact timing of embryo cleavages in a clinical setting. We propose a multivariable model based on our findings to classify embryos according to their probability of implantation. The efficacy of this classification will be evaluated in a prospective randomized study that ultimately will determine if implantation rates can be improved by time-lapse analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
809
7
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 772 publications
(890 citation statements)
references
References 47 publications
27
809
7
16
Order By: Relevance
“…Their paired RCT study also used the standard morphologic criteria for the selection of the embryos for transfer. During the last 5 years, image capturing with timelapse devices was introduced into in vitro fertilization (IVF) labs, offering a non-invasive method to monitor and analyze the full course of embryo development in real time without interfering with the optimal culture conditions [16,17]. Morphokinetic studies have already shown that embryos with high implantation potential cleave in specific patterns and similar timings [18][19][20][21][22][23].…”
Section: % Of All Biopsy Procedures Performed In Europe Betweenmentioning
confidence: 99%
“…Their paired RCT study also used the standard morphologic criteria for the selection of the embryos for transfer. During the last 5 years, image capturing with timelapse devices was introduced into in vitro fertilization (IVF) labs, offering a non-invasive method to monitor and analyze the full course of embryo development in real time without interfering with the optimal culture conditions [16,17]. Morphokinetic studies have already shown that embryos with high implantation potential cleave in specific patterns and similar timings [18][19][20][21][22][23].…”
Section: % Of All Biopsy Procedures Performed In Europe Betweenmentioning
confidence: 99%
“…In consequence, various new morphological and morphokinetic markers (time to cleavage, duration of cell cycle, synchronization of division or the timepoint when the embryo has reached a certain stage of development) evaluated by TLC were associated with viability and competence of the embryo. Based on a large amount of data generated by time-lapse incubators, several (multivariable) prediction models for an optimal selection were published [13][14][15][16][17]. Those embryos that reveal a deviation of these selection criteria were regularly discarded.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the study was to analyze how spermatozoa influence the outcome in terms of development to the blastocyst stage of embryos that fulfill (or not) the morphokinetic criteria according to recently postulated embryo selection models [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The zygote typically undergoes the first cleavage 20 to 27 h after insemination [2][3][4]. Using the evolving technology of timelapse imaging, it has been postulated that time intervals between cleavages, rather than fixed time limits for cell division, can predict embryo viability [5][6][7][8] . However, a consensus remains that embryos that follow the Baverage^growth curve for the normal development of the early human embryo (i.e., reach the four-cell stage by 44 h, and the eight-cell stage by 68 h) are those of highest quality [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using the evolving technology of timelapse imaging, it has been postulated that time intervals between cleavages, rather than fixed time limits for cell division, can predict embryo viability [5][6][7][8] . However, a consensus remains that embryos that follow the Baverage^growth curve for the normal development of the early human embryo (i.e., reach the four-cell stage by 44 h, and the eight-cell stage by 68 h) are those of highest quality [7,9,10]. While recent studies have investigated the value of time-lapse imaging for embryo assessment and selection [reviewed by 6] standard morphological evaluation remains an important approach for evaluating embryo quality in IVF programs, particularly for those that lack time-lapse imaging systems.…”
Section: Introductionmentioning
confidence: 99%